Ontology modelling of multimodality image retrieval system for sport news domain - Mohd Khalid, Yanti Idaya Aspura; Mohd Noah, Shahrul Azman (2011)
Sharing common understanding of the structure of information among people, enable reuse of domain ontology and make domain assumption explicit are the reasons why we develop the multimodality image retrieval system. Sport News Ontology is the explicit formal specification of terms in the sport news domain and relation among them. We incorporate the terms with the "garden resource" in DBpedia to enrich our multimodality ontology and improve the performance of image retrieval system.